Cotton Knit Fabric Dyed with Natural Indigo and UV Protection - Pupatana, Oiytip (Progress in Applied Science and Technology, 2019)
The main objective of this research were to 1) study knit fabric structure, physical properties and color values of cotton knit fabric structure undyed (white color) with the cotton knit fabric dyed with natural indigo and 2) compare the effectiveness in UV protection of cotton knit fabric structure undyed (white color) with the cotton knit fabric dyed with natural indigo. Physical properties tested stitch density, fabric thickness, bursting strength, air permeability values were measured before and after washing, color values tested L* a* b* C* and h* values and the effectiveness in UV protection of cotton knit fabric structure undyed (white color) with the cotton knit fabric dyed with natural indigo was then measured as follows: ultraviolet protection factor (UPF), percentage of UVA and UVB transmittance, and percentage of UVA and UVB blockage values were measured before washing, after five washing and 10-hour light exposure in both dry and wet conditions. It was found that the stitch density values of the cotton knit fabric dyed with natural indigo were a little greater than those of the cotton knit fabric structure undyed (white color) when measured before washing while their fabric thickness values of the cotton knit fabric dyed with natural indigo were a higher than those of the cotton knit fabric structure undyed (white color) when measured after washing while their bursting strength values of the cotton knit fabric structure undyed (white color) were a higher than the cotton knit fabric dyed with natural indigo when measured both before and after washing, and air permeability values the cotton knit fabric dyed with natural indigo indigo were a higher than those of the cotton knit fabric structure undyed (white color) when measured both before and after washing. It was also found that the cotton knit fabric structure undyed (white color) showed unprotect levels of effectiveness in UV protection when tested before and after laundering, light exposure in both dry and wet conditions. While the cotton knit fabric dyed with natural indigo, it was also found that showed very good to excellent levels of effectiveness in UV protection when tested before and after laundering, light exposure in both dry and wet conditions.